Protein adsorption and activity on carbon xerogels with narrow pore size distributions covering a wide mesoporous range. (July 2017) - Ramírez-Montoya, Luis A.; Concheso, Alejandro; Alonso-Buenaposada, Isabel D.; García, Héctor; Angel Menéndez, J.; Arenillas, Ana; Montes-Morán, Miguel A.
Abstract: Four carbon xerogels (CXs) were used to study the effect of the average pore size (APS) on the adsorption and activity of cytochrome c (cyt c ). Pore size distributions of the CXs were relatively narrow with APSs covering the whole mesoporosity range (5, 15, 30 and 55 nm), as determined by mercury porosimetry. Selected techniques verified that all carbons were identical in terms of composition and surface chemistry. The best APS for cyt c adsorption (in terms of capacity) was 30 nm, with loadings of 180 mg of protein (g of support) −1 . The CX with APS of 15 nm also hosted high amounts of cyt c, followed by the material with 55 nm. The CX with 5 nm APS did not adsorb cyt c . The pH of adsorption had little effect on the final amount adsorbed, thus stressing the hydrophobic nature of the protein/carbon surface interaction. The activity of the resulting materials towards the ABTS oxidation was similar regardless the amount of cyt c adsorbed on their surface/pores. Their performance in successive cycles of re-use was different depending on the carbon support; xerogels bearing APSs ≥15 nm presented an increasing activity with increasing the number of cycles. Graphical abstract: